Digital Well-Being Tourism in the Fourth Industrial Revolution - Debasa, Felipe (Journal of Tourism, Sustainability and Well-being, 2022)
The current world changes rapidly. This period of great and rapid transformations is known as the IV Industrial Revolution which is characterized by the fact that industries, processes and stocks are linked in a network globally. It is demonstrated in this article with historical foundations that societies are not prepared for those rapid changes and transformations. Sometimes it takes a few generations for society’s changes to be assimilated. However, technology development boots innovation and society’s transformation within months. As a result, new mental and physical illnesses appear related to technology, such as techno-anxiety and technostress that are directly linked to the concept of digital well-being. Now, the only way that society has to fight against these pathologies is learning and training using new processes and approaches. As the current society cannot stop using technology, the society should take care of digital well-being. In this study, one of the ways to prevent or minimize pathologies caused by the excessive use of technological applications in tourism is presented and discussed. Theoretical and practical implications are presented to decrease health pathologies intensity caused by the used of technological devices.